Crown dilaceration - Ghimire, N; Rao, A (Health Renaissance, 2013)
Dilaceration of teeth can occur as a result of trauma to its primary predecessors. Root dilaceration is more common than crown dilacerations. A rare case of crown dilaceration of maxillary permanent central incisor has been reported in this article. Health Renaissance, January-April 2013; Vol. 11 No.1; 86-88 DOI: http://dx.doi.org/10.3126/hren.v11i1.7609